Impact of kyoto protocol and institutional factors on carbon dioxide emissions in Asia-Pacific Region / Siti Ayu Jalil, Muzafar Shah Habibullah - Jalil, Siti Ayu; Habibullah, Muzafar Shah (Faculty of Business Management, UiTM Puncak Alam, 2013)
This study investigates the impact of Kyoto Protocol and four institutional factors i.e. political stability, property rights, corruption and freedom of trade on the growth of per capita CO² emissions in Asia and the Pacific region for the period of 1971-2009. The region consists of East Asia, South Asia and the Pacific islands are the fastest growing economic region and the source of global greenhouse gas emissions. A dynamic panel data model based on the Generalised Method of Moments (GMM) technique is utilized to examine these impacts. The findings indicate only Kyoto commitment (Kcom), Kyoto Clean Development Mechanism (Kcdm) and Corruption (COR) describe statistically significant positive effects on CO² emissions